Humanistic Curriculum Model In Arabic Language Learning At Private MTs Yapena Lhokseumawe City - Ikhsan, Arief Maulana; Solihah, Mamluatu (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
The objective of this research is to elucidate the humanistic curriculum development model and its utilization in crafting Arabic teaching resources. The research methodology employed is descriptive qualitative, adopting a case research approach at Private MTs of Yapena Lhokseumawe. The research encompasses several aspects: 1) understanding the concept of humanistic curriculum development, 2) implementing humanistic curriculum in Arabic teaching resources, 3) executing activities at Private MTs of Yapena, and 4) gathering insights through interviews and observations at Private MTs of Yapena Lhokseumawe. Data collection was conducted through observations and interviews with both teachers and students of Private MTs of Yapena. The collected data underwent analysis to condense and articulate outcomes derived from the fieldwork. The research revealed that the application of the humanistic curriculum development model in crafting Arabic teaching resources yielded favorable outcomes, enhancing both cognitive and non-cognitive abilities among students. By centering learning around students and providing them with opportunities to foster their innate potential and enhance creativity, the humanistic curriculum development model elicited a notable surge in student engagement, with a 60% increase in learning competencies observed post-research.   Keywords: humanistic, curriculum development, Arabic language